Gardening with native plants of the Pacific Northwest - Kruckeberg, Arthur R.; Chalker-Scott, Linda (Linda K.) (University of Washington Press, 2019)
The Pacific Northwest abounds with native plants that bring beauty to the home garden while offering food and shelter to birds, bees, butterflies, and other wildlife. Elegant trilliums thrive in woodland settings. Showy lewisias stand out in the rock garden. Hazel and huckleberry number among the delights of early spring, while serviceberry and creek dogwood provide a riot of fall color. Gardening with Native Plants of the Pacific Northwest is the essential resource for learning how to best use this stunning array.